"Flipping or flapping?" investigating engineering students' experience in flipped classrooms. Issue 4 (5th November 2018) - Chew, Esyin; Jones, Lim Jen Nee; Wordley, Scott
Abstract : Purpose: This study has explored the flipped classroom model in a private university in Malaysia. It aims to present a flipped classroom intervention for engineering education innovation. Design/methodology/approach: The research (1) revisited prominent educational theories for a flipping or flapping pedagogy, (2) implemented and explored the flipped classroom experiences in one engineering subject using the action inquiry method with thematic analysis and (3) reflectively evaluated both students' and educators' "flipping or flapping experience". Findings: The responses of the research participants are analysed and used to develop the flipping or flapping classroom principles and an ideal flipped classroom model. From passive lectures to active learning with collaborative discourse and reflective communication, flipping the classroom can offer a seamless learning experience. Research limitations/implications: The flipped classroom model can provide good reference for other educational researchers who intended to conduct a flipped classroom. However, the small sample size with qualitative method and thematic analysis useds led to considerable theoretical development, but it may not achieve the validity standards to generalise the findings. Further empirical investigation with a systematic controlled group is recommended for future work across disciplines for extrapolation. Originality/value: This is a genuine case study with an identified innovative teaching need to investigate how flipped classrooms can be enabled and enhanced in engineering education innovation.